White matter hyperintensities on brain magnetic resonance in systemic sclerosis. Issue 5 (15th April 2005) - Sardanelli, F; Iozzelli, A; Cotticelli, B; Losacco, C; Cutolo, M; Sulli, A; Nobili, F; Rodriguez, G
Abstract : Objective: To evaluate the brain status of patients with systemic sclerosis (SSc). Methods: Fourteen female patients with SSc aged 24–74, with a disease duration of 1–12 years and without other relevant systemic diseases, were enrolled. All patients and an age matched female control group (CG) of 14 clinically normal subjects, underwent brain magnetic resonance examination at 1.5 T; spin echo proton density weighted images were evaluated. Mann-Whitney U and Spearman rank correlation tests were used for statistical analysis. Results: 170 white matter hyperintensities ⩾2 mm in diameter were counted in the patient group (range 0–75, mean 12.1, median 4.5), only 13 in the CG (0–2, 0.9, 1, respectively), with a significant difference (p = 0.011). Moreover, 208 white matter hyperintensities <2 mm were found in the patient group (0–38, 14.9, 8, respectively), only 31 in the CG (0–7, 2.0, 1, respectively), with a significant difference (p = 0.006). No statistically significant correlation between the number of hyperintensities and either patient's age or disease duration was observed. Conclusion: White matter hyperintensities are more common in patients with SSc than in a CG. These findings might be related to obliterative microvascular processes due to the disease. Early brain involvement in patients with SSc may occur.